On the Thermomechanics of Hadrons and Their Mass Spectrum - Leonardo Chiatti (Particles)
A little-known thermomechanical relation between entropy and action, originally discovered by Boltzmann in the classical domain, was later reconsidered by de Broglie in relation to the wave–particle duality in the free propagation of single particles. In this paper, we present a version adapted to the phenomenological description of the hadronization process. The substantial difference with respect to the original de Broglie scheme is represented by the universality of the temperature at which the process occurs; this, in fact, coincides with the Hagedorn temperature. The main results are as follows: (1) a clear connection between the universality of the temperature and the existence of a confinement radius of the color forces; (2) a lower bound on the hadronic mass, represented by the universal temperature, in agreement with experimental data; and (3) a scale invariance, which allows the reproduction of the well-known hadronic mass spectrum solution of the statistical bootstrap model. The approach therefore presents a heuristic interest connected to the study of the strong interaction.